Blood group genotyping in alloimmunized multi‐transfused thalassemia patients from Iran. Issue 7 (8th May 2021) - Sarihi, Reyhaneh; Oodi, Arezoo; Dadkhah Tehrani, Raziyeh; Jalali, Seyedeh Farzaneh; Mardani, Fahimeh; Azarkeivan, Azita; Gudarzi, Samira; Amirizadeh, Naser
Abstract: Objectives: Serological methods may not be reliable for RBC antigen typing, especially in multi‐transfused patients. The blood group systems provoking the most severe transfusion reactions are mainly Rh, Kell, Kidd, and Duffy. We intended to determine the genotype of these blood group system antigens among Iranian alloimmunized thalassemia patients using molecular methods and compare the results with serological phenotyping. Methods: Two hundred patients participated in this study. Blood group phenotype and genotype were determined using the serological method and PCR‐SSP, respectively. The genotypes of patients with incompatibility between phenotype and genotype were re‐evaluated by RFLP‐PCR and confirmed by DNA sequencing. Results: Discrepancies between phenotype and genotype results were found in 132 alleles and 83 (41.5%) patients; however, there was complete accordance between the three genotyping methods. Most discrepancies were detected in Rh and Duffy systems with 47 and 45 cases, respectively, and the main discrepancy was in the FY*B/FY*B allele when serologically showed Fy(a+b+). All 39 undetermined phenotypes, due to mixed‐field reactions, were resolved by molecular genotyping. Conclusion: Molecular genotyping is more reliable compared with the serological method, especially in multi‐transfused patients. Therefore, the addition of blood group genotyping to serological assays can lead to an antigen‐matched transfusion in these patients. Abstract : Molecular genotyping is more reliable compared with the serological method, especially in multi‐transfused patients. Therefore, the addition of blood group genotyping to serological assays can lead to a better‐matched transfusion in these patients.